355 The risk of injuries in children with Attention deficit-hyperactivity disorder (ADHD) in England. (1st September 2016) - Prasad, Vibhore; Sayal, Kapil; West, Joe; Kendrick, Denise
Abstract : Background: Attention deficit-hyperactivity disorder (ADHD) is a common in children with a prevalence of 5%. Injuries are common and are a leading cause of morbidity and mortality in England and worldwide. ADHD may be associated with an increased risk of injuries but accurate and detailed risk estimates are lacking. Methods: A cohort study was conducted using primary care and hospital records from the Clinical Practice Research Datalink (CPRD) (1998 to 2012). All children with ADHD (aged 3 to 17 years) were frequency-matched, by age band, to up to twenty children without ADHD. Hazard ratios for (long bone) fractures, thermal injuries and poisonings were estimated using Cox regression and adjusted for age, sex, strategic health authority region, area-level deprivation quintile (measured using Index of Multiple Deprivation) and the calendar year when the child entered the study. Results: There were 15, 737 children with and 291, 894 without ADHD. 84.6% with ADHD were boys compared to 50.7% without ADHD. The adjusted risk of fractures in children with ADHD was 28% greater than in children without (HR = 1.28 (1.22 to 1.35)). The adjusted risk of thermal injuries in children with ADHD was more than double the risk in children without (HR = 2.04 (1.80 to 2.31)). The adjusted risk of poisonings was nearly 4 times greater in children with ADHD compared to children without (HR = 3.99 (3.58 to 4.44)). The adjusted risk of long bone fractures was similar to the risk of any fractures (HR = 1.23 (1.16 to 1.31)). Conclusions: Children with ADHD are at a greater risk of fractures, thermal injuries and poisonings than children without. All services involved in the care and education of children with ADHD should be aware of the risks. The estimated risks of injury should be communicated to children and their parents at the time of diagnosis, medication reviews and follow-up visits.